2021
DOI: 10.2147/hiv.s281281
|View full text |Cite
|
Sign up to set email alerts
|

Rate of HIV Seroconversion Among Seronegative Male Partners Living with HIV Positive Women in Addis Ababa, Ethiopia, 2019: A Retrospective Cohort Study

Abstract: Objective This study aimed to assess rate of HIV seroconversion and predictors among seronegative male partners living with HIV-positive women in Addis Ababa, Ethiopia, 2019. Methods Institutional-based retrospective cohort was used to conduct the study. All eligible 227 sample medical records were used for the study. Kaplan–Meier analysis was used to estimate seroconversion time. Cox proportional-hazard regression was used to identify predictor variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…This finding revealed that those spousal partners whose index cases started ART immediately as on meeting the eligibility criteria criteria were 83% less likely to be seropositive than those whose index partners didn’t start immediately. This finding is consistent with the findings of a study conducted in Addis Ababa, Ethiopia [ 22 ]. This might be because ART initiation based on the eligibility criteria could lead to increase in index case CD4 count and VL suppression that decreases HIV transmission to spousal partners This study showed that spousal partners whose index cases who were at WHO clinical stage III or IV at enrollment were 7.25 times more likely to be seropositive than spousal partners whose index cases who were WHO clinical stage I or II.…”
Section: Discussionsupporting
confidence: 93%
“…This finding revealed that those spousal partners whose index cases started ART immediately as on meeting the eligibility criteria criteria were 83% less likely to be seropositive than those whose index partners didn’t start immediately. This finding is consistent with the findings of a study conducted in Addis Ababa, Ethiopia [ 22 ]. This might be because ART initiation based on the eligibility criteria could lead to increase in index case CD4 count and VL suppression that decreases HIV transmission to spousal partners This study showed that spousal partners whose index cases who were at WHO clinical stage III or IV at enrollment were 7.25 times more likely to be seropositive than spousal partners whose index cases who were WHO clinical stage I or II.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings show a high prevalence (72.0%) of PLHIV in a relationship with HIV seronegative/unknown partners, similar to other studies that described representative rates of PLHIV in sexual serodifferent relationships worldwide [2,3,8,19,20].…”
Section: Discussionsupporting
confidence: 91%
“…These combined prevention strategies make it possible to expand risk management among couples living in the HIV context. The diversity of strategies allows greater freedom of choice for the best preventive methods and benefits different marital arrangements considering HIV serodiscordant couples [7,8]. Therefore, counseling and guidance about sexual HIV prevention for serodiscordant couples is indispensable overall [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Bantigen & Cols. (2021), demonstrated a reduction in the transmission of infection between serodiscordant partners can be up to 95% while using Pre-Exposure Prophylaxis (PrEP) as a Bridge to ART strategy [ 43 ]. However, ART therapy has transformed HIV infection to a chronic disease, with autonomic dysfunction, as previously described, which is associated with cardiac impairment, especially in low CD4 counts [ 6 , 21 , 45 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cardiac autonomic function has been studied through computerized analysis of heart rate variability (HRV) in the time- and frequency- domains. This method is a non-invasive test, which is easy to apply, reliable, and allows for the characterization of the absolute and relative modulation of the sympathetic and parasympathetic components of the cardiac ANS [ 29 , 43 46 ].…”
Section: Introductionmentioning
confidence: 99%